2022
DOI: 10.1038/s41598-022-16102-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking analysis and evaluation of the antimicrobial properties of the constituents of Geranium wallichianum D. Don ex Sweet from Kashmir Himalaya

Abstract: Geranium wallichianum D. Don ex Sweet is a well-known medicinal plant in Kashmir Himalya. The evidence for its modern medicinal applications remains majorly unexplored. The present study was undertaken to elucidate the detailed antimicrobial promises of different crude extracts (methanolic, ethanolic, petroleum ether, and ethyl acetate) of G. wallichainum against common human bacterial and fungal pathogens in order to scientifically validate its traditional use. The LC–MS analysis of G. wallichainum yielded 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Furthermore, this compound makes hydrophobic stacking interactions with Trp 374 and Thr 550 which enhance the C7 binding to the active site of PBP ( Figure 6 D). Interestingly, these results showed that compound C7 interacts with significant amino acids Ser 337 (catalytic amino acid), Trp 374 and Tyr 568 as designated by Mir et al, (2022) [ 31 ]. According to the results found by Damasceno, J.P.L., in 2017, C7 also established interactions with key amino acids Ser 395, Ser 548, and Thr 550 [ 28 ].…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, this compound makes hydrophobic stacking interactions with Trp 374 and Thr 550 which enhance the C7 binding to the active site of PBP ( Figure 6 D). Interestingly, these results showed that compound C7 interacts with significant amino acids Ser 337 (catalytic amino acid), Trp 374 and Tyr 568 as designated by Mir et al, (2022) [ 31 ]. According to the results found by Damasceno, J.P.L., in 2017, C7 also established interactions with key amino acids Ser 395, Ser 548, and Thr 550 [ 28 ].…”
Section: Resultsmentioning
confidence: 97%
“…The obtained value was higher than that measured by Mir et al (2022). In fact, the highest binding energy to PBP was measured for elatine at −9.2 kcal/mol [ 31 ]. The binding energy is directly related to the stability of the complex formed between the ligand and the target protein [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural active molecules like quercetin, eugenol and kaempferol have been reported to bind effectively to PBPs [ 57 , 58 ]. It is worth noting that kaempferol exhibits higher specificity toward PBPs by interacting with crucial amino acids [ 59 ]. This suggests that the small molecules in KLSC have the potential to disrupt E. coli cell wall formation and exhibit antimicrobial properties by targeting PBPs.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of new cancer treatments is still regarded as an active research area despite the great advance in the area of chemotherapy. Medicinal plants are regarded as a renewable source of bioactive compounds that can be exploited in the treatment of various ailments including cancer ( Tariq et al, 2021 ; Mir et al, 2022a ; Mir et al, 2022b ). Phytochemicals play an important role in the initiation, development, and advancement of carcinogenesis, as well as in suppressing or reversing the early stages of cancer or the invading potential of premalignant cells and also regulate cell proliferation and apoptosis signalling pathways in transformed cells ( George et al, 2021 ; Bhat et al, 2022a ; Bhat et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%